Extensor Mechanism Reconstruction for Chronic Patellar Tendon Tears. Issue 2 (February 2023) - Cimino, Addison; Wall, Kevin C.; Elphingstone, Joseph; Paul, Kyle; Arguello, Alexandra M.; Casp, Aaron; Brabston, Eugene; Ponce, Brent; Momaya, Amit
Abstract : Although much has been published on the repair of acute patellar tendon disruptions in native knees and the reconstruction of the extensor mechanism in the prosthetic knee, there is a dearth of literature on chronic patellar tendon reconstruction in the native knee. The aim of this systematic review was to synthesize the outcomes in the existing literature on this important topic. Secondarily, the various surgical techniques and graft options for this procedure are summarized. Abstract: Objectives: Reconstruction for a chronic patellar tendon rupture in a native knee is an uncommon surgical procedure. Although there have been case series investigating patient-reported outcomes, there is no systematic review of these studies to date. The purpose of this review is to synthesize the literature on this procedure to better understand its outcomes, complications, and surgical technique options. Methods: A systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to identify studies that reported outcomes and techniques of patellar tendon reconstruction for chronic disruption in native knees. Searches were conducted through MEDLINE using PubMed, Cochrane Database of Systematic Reviews, and clinicaltrials.gov . Results: Ten studies with 103 patients and 105 knees were included. Results for nonnative (arthroplasty) knees were excluded. The mean patient age was 40.3 years, and the mean postsurgical follow-up time was 53.8 months. Of the 105 knees, 75% received a hamstring tendon graft, whereas 13% received a bone-tendon-bone graft and 7% received a whole extensor mechanism allograft. The mean preoperative range of motion was 113.8°, which improved to 126.0° postoperatively. The mean preoperative Lysholm score was 58.6, which improved to 86.0 postoperatively; 100% of patients returned to their normal work activities and 76% returned to their prior level of physical activity. There were no major complications reported in any of the included studies. Conclusions: Chronic patellar tendon disruption in a native knee is an uncommon injury that can result in significant limitations for patients. Although more research is needed to better elucidate which graft is best, outcomes after patellar tendon reconstruction for chronic tears appear to be satisfactory with current techniques.